Epidemiology of Respiratory Syncytial Virus Among All Ages in 2023 in Beijing, China - Xue-Kai Liu; Mei-Yan Xu; Ming-Jian Bai; Lei Shang; Qin-Yi Ma; Guo-Wei Liang; Qing-Bin Lu (Advances in Public Health, 2024)
Few studies have investigated respiratory syncytial virus (RSV) infection across all age groups in the postpandemic era of coronavirus disease 2019 (COVID-19). The study aimed to characterize the epidemiology of RSV in all ages in Beijing during 2023. Medical records and RSV testing results of outpatients and inpatients from March to December in 2023 were extracted from the Aerospace Center Hospital. Among 8594 patients, the detection rate of RSV was 4.44% (95% confidence interval [CI] 4.02%−4.90%). The detection rates of RSV in patients aged ≤5 years, 5–18 years, 18–60 years, and >60 years were 19.06%, 4.72%, 1.86%, and 1.78% (p <0.001), respectively. The peak month for RSV detection rate was in May (15.1%), followed by April (10.9%). RSV detection rate declined sharply in patients aged ≤20 years (annual percent change [APC] = −68.32, 95% CI = −81.6 to −45.5, p=0.002) and then maintained at a steady level (APC = 0.49, 95% CI = −14.5–18.1, p=0.944). In April and May, children had higher RSV detection rates than adult in both the pneumonia and nonpneumonia groups (p <0.05). Multivariable analysis showed that younger children (odds ratio [OR] = 13.775, 95% CI 10.339–18.354 for ≤5 years’ group; OR = 2.675, 95% CI 1.859–3.849 for 5–18 years’ group compared to the >60 years’ group) and those tested after September (OR = 1.317, 95% CI 1.050–1.653) had higher RSV detection rates. The COVID-19 epidemic had a temporary effect on RSV transmission, delaying the peak of RSV detection rate in children but not in adults.